2019
DOI: 10.1111/ctr.13617
|View full text |Cite
|
Sign up to set email alerts
|

Early experiences of independent advocates for potential HIV+ recipients of HIV+ donor organ transplants

Abstract: Background HIV+ to HIV+ solid organ transplants in the United States are now legally permitted. Currently, these transplants must adhere to the HIV Organ Policy Equity (HOPE) Act Safeguards and Research Criteria that require the provision of an independent recipient advocate. Having a designated advocate for recipients is a novel requirement for solid-organ transplant programs. The objective of this study was to understand the experiences of the first advocates serving this role. Methods We conducted 15 semi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
(22 reference statements)
0
4
0
Order By: Relevance
“…This finding is consistent with the results of an interview study with HOPE IAs, which found that their role was not clearly defined or understood. 32 These emerging data may challenge prior conceptual scholarship asserting the importance of independent advocates in the protection of HIV D + /R + transplant recipients. 13 , 17 Consequently, additional data would likely be useful in informing future conceptual and policy deliberations regarding IAs in this setting.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with the results of an interview study with HOPE IAs, which found that their role was not clearly defined or understood. 32 These emerging data may challenge prior conceptual scholarship asserting the importance of independent advocates in the protection of HIV D + /R + transplant recipients. 13 , 17 Consequently, additional data would likely be useful in informing future conceptual and policy deliberations regarding IAs in this setting.…”
Section: Discussionmentioning
confidence: 99%
“…PROMETHEUS was developed as part of a larger multidisciplinary project aimed at understanding the ethical, legal and social issues associated with HIV D+/R+ transplantation. The larger project includes in-depth interviews with recipients of HIV D+/R+ transplants, potential HIV+ living donors [ 21 ] and independent recipient advocates [ 22 ] as well as a quantitative survey of transplant candidates living with HIV on the organ transplant waitlist regarding their willingness to accept HIV D+/R+ transplants [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…The additional psychosocial strain of deciding between remaining on the waiting list or taking an organ from a higher risk donor increases the difficulty of obtaining informed consent for transplant. The HOPE Act mandates that Independent Recipient Advocates (HIRA) must be involved to navigate these challenging decisions with patients [44]. HIRAs typically have backgrounds in nursing, social work, or medicine.…”
Section: Comparative Cost Of Hiv Treatment With and Without Transplantmentioning
confidence: 99%
“…Duties as the HIRA are often added on to primary clinical roles. In some instances, an individual HIRA has assisted with over 15 evaluations [44]. Thus far, HIRAs have been independent of the transplant team, and are unpaid volunteers.…”
Section: Comparative Cost Of Hiv Treatment With and Without Transplantmentioning
confidence: 99%